The magmatic plumbing system of the Askja central volcano, Iceland, as imaged by seismic tomography. Issue 10 (5th October 2016) - Greenfield, Tim; White, Robert S.; Roecker, Steven
Abstract: The magmatic plumbing system beneath Askja, a volcano in the central Icelandic highlands, is imaged using local earthquake tomography. We use a catalog of more than 1300 earthquakes widely distributed in location and depth to invert for the P wave velocity ( Vp ) and the Vp / Vs ratio. Extensive synthetic tests show that the minimum size of any velocity anomaly recovered by the model is ~4 km in the upper crust (depth < 8 km below sea level (bsl)), increasing to ~10 km in the lower crust at a depth of 20 km bsl. The plumbing system of Askja is revealed as a series of high‐ Vp / Vs ratio bodies situated at discrete depths throughout the crust to depths of over 20 km. We interpret these to be regions of the crust which currently store melt with melt fractions of ~10%. The lower crustal bodies are all seismically active, suggesting that melt is being actively transported in these regions. The main melt storage regions lie beneath Askja volcano, concentrated at depths of 5 km bsl with a smaller region at 9 km bsl. Their total volume is ~100 km 3 . Using the recorded waveforms, we show that there is also likely to be a small, highly attenuating magmatic body at a shallower depth of about 2 km bsl. Key Points: Low velocities in the crust delineate the magmatic plumbing system beneath Askja volcano in Iceland Primary magma storage region is at a depth of 5 km bsl but extends into the lower crust where melt movement generates microearthquakes Melt is distributed in discrete regions throughout the crust to depths of over 20 km